The effect of health education video on the prevention behaviour of sexually transmitted infections (STI’s) in adolescent - Nada Sari; Elfrida Simamora; Zulaika Harissya (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Most sexually transmitted infections (STIs) in adolescents are similar to those in young adults. Adolescence is a phase of life when adolescents reach sexual maturity and begin to make decisions and choices regarding reproductive health. Several factors contribute to adolescents' vulnerability to STIs, including having sexual intercourse, engaging in same-sex sexual relations, and having more than one sexual partner. Common STIs in adolescents include chlamydia, gonorrhea, syphilis, genital herpes, HIV/AIDS, genital warts, pubic lice, and trichomoniasis. Unprotected sexual intercourse among adolescents can have significant impacts. Therefore, it is crucial to provide education to adolescents using learning media through health education programs. Purpose: To identify the effect of health education videos on STI prevention behaviors in adolescents. Method: This study used a quasi-experimental design with a control group. The sample consisted of 169 participants selected using stratified random sampling. Data were collected through pre-tests and post-tests, while data processing was performed using SPSS software with the Wilcoxon test. This study was conducted in three private high schools in Bekasi City from June to July 2024. Results: This study obtained a p-value of 0.000 ≤ 0.005, indicating that health education videos influenced sexually transmitted infection (STI) prevention behavior in adolescents. Conclusion: Health education videos were found to influence sexually transmitted infection (STI) prevention behavior in adolescents. Suggestion: Adolescents should be more aware of the importance of independent STI prevention by seeking the latest information about STIs. Keywords: Adolescents; Health Education; Preventive Behavior; Sexually Transmitted Infections.